Public Theology in the Context of the Religious Dualization Phenomenon in Multiple Modernities - Teixeira, Alfredo (International journal of public theology, 2022)
This article aims to analyze the tasks of public theology concerning the religious phenomenon in a context of multiple modernities. The interaction of religion and public space may take the form of a disjunction between public and private that strengthens the rigid discourse of religious identity against a common project of society. In this context, the place of religion in the public life becomes a significant challenge for public theology. Therefore, in dialogue with the theoretical perspectives of Jürgen Habermas, David Tracy, Michel de Certeau, and Pope Francis, this text proposes a movement towards a complex and interdisciplinary approach that values a shared humanity and responsibility with the common home.